Gluconate-derived hard carbon negative electrode material, preparation method thereof, negative electrode and lithium ion battery

Through the method of removing metal elements in staged carbonization and acid washing, the lithium storage capacity and circulation performance of hard carbon negative electrode materials are improved, and the problem of insufficient performance of existing hard carbon materials is solved.

CN119461327AActive Publication Date: 2025-02-18CHONGQING INNOVATION CENTER OF BEIJING INSTITUTE OF TECHNOLOGY +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411656538.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The existing hard carbon negative electrode materials have low lithium storage capacity, and the rate performance and cycling performance need to be improved.

Method used

Carbonization is carried out in stages and metal elements in the material are removed by acid washing during the two carbonizations, introducing rich pore structures and increasing lithium storage sites.

Benefits of technology

The excellent charging specific capacity and cycling efficiency of hard carbon negative electrode materials are achieved. The charging specific capacity of the first week's charging and discharging cycle is not less than 320mAh/g, and the reversible specific capacity at 1C ratio is not less than 250mAh/g after 300 weeks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461327A_ABST
    Figure CN119461327A_ABST
Patent Text Reader

Abstract

The invention relates to the field of batteries, and discloses a gluconate-derived hard carbon negative electrode material, a preparation method of the gluconate-derived hard carbon negative electrode material, a negative electrode and a lithium ion battery. And performing second heat treatment on the intermediate in an inert gas atmosphere to obtain the hard carbon negative electrode material. The process of the first heat treatment comprises a first heat treatment step and a second heat treatment step, the temperature of the first heat treatment step is 400-600 DEG C, the time is 1-2 hours, and the temperature of the second heat treatment step is higher than that of the first heat treatment step; the second heat treatment process comprises a third heat treatment step and a fourth heat treatment step, the temperature of the third heat treatment step is higher than the temperature of the second heat treatment step and lower than the temperature of the fourth heat treatment step, the temperature of the fourth heat treatment step is 1300-1500 DEG C, and the time is 50-150 minutes. And higher lithium storage capacity is achieved in the ether-based electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of batteries, and in particular to a gluconate-derived hard carbon negative electrode material, a preparation method thereof, a negative electrode and a lithium ion battery. Background Art

[0002] With the rapid development of the global economy, people have gradually realized that fossil fuels are becoming increasingly depleted and their harm to the environment. The development of green, pollution-free renewable energy is an effective way to solve energy and environmental problems. In recent years, lithium-ion batteries have been widely used in portable electronic devices, electric vehicles and other fields due to their advantages such as high capacity and long cycle life. Since the development of lithium-ion batteries, a variety of positive electrode material systems have been studied. In the historical process of the birth and development of lithium-ion batteries, carbon negative electrode materials have played a significant role in improving battery energy storage performance, improving safety, and reducing costs, and have triggered a research and development boom in academic and industrial institutions around the world. At present, the negative electrode of commercial lithium-ion batteries is mainly graphite-based materials. According to the LiC between graphite layers, 6 Its theoretical specific capacity is only 372 mAh / g due to its lithium storage mechanism, and there is very limited room for improvement. In addition, the lithium diffusion between graphite layers also restricts its rate performance. It can be seen that with the increasing demand for battery energy and power performance in downstream applications, pure graphite-based negative electrode materials have become inadequate. As a new type of negative electrode material, hard carbon has a similar lithium potential to graphite and a higher specific capacity. More importantly, hard carbon is composed of a graphite-like microcrystalline structure and open angular microcrystals. This unique microcrystalline structure can not only provide more lithium storage sites, but also facilitate the deintercalation of lithium ions between graphite layers. Therefore, as a new generation of negative electrode materials for lithium-ion batteries, hard carbon has a very broad development prospect.

[0003] In recent years, significant progress has been made in the research of hard carbon anode materials, but many challenges / bottlenecks still exist: 1) the lithium storage capacity of most hard carbon materials is still low; 2) the rate performance and cycle performance need to be improved. Summary of the invention

[0004] The purpose of the present invention is to overcome the above problems existing in the prior art and provide a gluconate-derived hard carbon negative electrode material and a preparation method thereof, a negative electrode and a lithium ion battery. The hard carbon negative electrode material provided by the present invention has excellent charge specific capacity and cycle coulomb efficiency.

[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a method for preparing a hard carbon negative electrode material, wherein gluconate is subjected to a first heat treatment in an inert gas atmosphere, and then soaked in an acidic solution to remove metal elements to obtain an intermediate, and the intermediate is subjected to a second heat treatment in an inert gas atmosphere to obtain a hard carbon negative electrode material; The first heat treatment process includes: a first heat treatment and a second heat treatment performed sequentially, wherein the temperature of the first heat treatment is 400-600°C, the time is 1-2h, and the temperature of the second heat treatment is higher than the temperature of the first heat treatment; The second heat treatment process includes: a third heat treatment and a fourth heat treatment performed in sequence, wherein the temperature of the third heat treatment is higher than the temperature of the second heat treatment and lower than the temperature of the fourth heat treatment, and the temperature of the fourth heat treatment is 1300-1500°C and the time is 50-150min.

[0006] A second aspect of the present invention provides a hard carbon negative electrode material, which is prepared according to the preparation method described in the first aspect of the present invention.

[0007] The third aspect of the present invention provides a negative electrode, which comprises the hard carbon negative electrode material prepared by the preparation method described in the first aspect of the present invention or the hard carbon negative electrode material described in the second aspect of the present invention.

[0008] A fourth aspect of the present invention provides a lithium-ion battery, comprising the negative electrode described in the third aspect of the present invention.

[0009] The present invention performs carbonization in stages and removes metal elements in the material by pickling during the two carbonizations, so that a rich pore structure is introduced into the material, increasing lithium storage sites. A part of the introduced pores forms a closed-pore structure during the second carbonization, which is beneficial to improving the electrochemical performance of the material.

[0010] Compared with commercial graphite, the hard carbon material prepared by the present invention has a higher lithium storage capacity in an ether-based electrolyte. In addition, the present invention only includes two steps of carbonization and washing, and the process is simple, safe and low in cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 is a SEM image of the hard carbon negative electrode material prepared in Example 1 (scale is 10 μm); Figure 2 is a SEM image of the hard carbon negative electrode material prepared in Example 1 (scale is 1 μm); Figure 3 is an EDS image of the hard carbon negative electrode material prepared in Example 1; Figure 4 The first week charge and discharge curve of the hard carbon negative electrode material prepared in Example 1 after being assembled into a battery at a current density of 0.1C (1C=300mAh / g) in a voltage window of 0.01V~1.5V; Figure 5 This is the cycle curve of 1C current density in the voltage window of 0.01V~1.5V after the hard carbon negative electrode material prepared in Example 1 is assembled into a battery. DETAILED DESCRIPTION

[0012] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0013] The terms "first", "second", etc. are used to distinguish similar objects rather than to describe a specific order or sequence. It should be understood that the data used in this way are interchangeable where appropriate so that the embodiments of the present application can be implemented in an order other than those illustrated or described herein, and the objects distinguished by "first", "second", etc. are generally of the same type, and the number of objects is not limited. For example, the first object can be one or more.

[0014] In addition, the term "and / or" in the specification and claims is used to describe the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0015] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0016] The first aspect of the present invention provides a method for preparing a hard carbon negative electrode material, wherein gluconate is subjected to a first heat treatment in an inert gas atmosphere, and then soaked in an acidic solution to remove metal elements to obtain an intermediate, and the intermediate is subjected to a second heat treatment in an inert gas atmosphere to obtain a hard carbon negative electrode material; The first heat treatment process includes: a first heat treatment and a second heat treatment performed sequentially, wherein the temperature of the first heat treatment is 400-600°C, the time is 1-2h, and the temperature of the second heat treatment is higher than the temperature of the first heat treatment; The second heat treatment process includes: a third heat treatment and a fourth heat treatment performed in sequence, wherein the temperature of the third heat treatment is higher than the temperature of the second heat treatment and lower than the temperature of the fourth heat treatment, and the temperature of the fourth heat treatment is 1300-1500°C and the time is 50-150min.

[0017] In some embodiments, preferably, the difference between the temperature of the second heat treatment and the temperature of the first heat treatment is not less than 200°C.

[0018] In some embodiments, preferably, the difference between the temperature of the third heat treatment and the temperature of the second heat treatment is not less than 100°C.

[0019] In some embodiments, preferably, the difference between the temperature of the fourth heat treatment and the temperature of the third heat treatment is not less than 100°C.

[0020] In some embodiments, preferably, the temperature of the second heating step is 800-1000° C., and the time is 1-2 h.

[0021] In some embodiments, preferably, the temperature of the third step heat treatment is 900-1200° C., and the time is 1-2 h.

[0022] In some embodiments, preferably, the heating rate of the first step heat treatment is 5-15 / °C min.

[0023] In some embodiments, preferably, the heating rate of the fourth step heat treatment is 1-5°C / min.

[0024] In some embodiments, preferably, the heating rate of the second heat treatment is 5-15° C. / min.

[0025] In some embodiments, preferably, the heating rate of the third step heat treatment is 5-10° C. / min.

[0026] The heat treatment temperature, time, and heating rate at different stages are directly related to the carbonization degree of the material, the amount of porosity introduced, and are directly related to the increase in lithium storage sites. The heat treatment time, temperature, etc. at each stage provided by the present invention can further improve the above-mentioned performance.

[0027] The temperature of the first step heat treatment can be any value within the numerical range composed of any two numbers of 400℃, 450℃, 500℃, 550℃, and 600℃; the time of the first step heat treatment can be any value within the numerical range composed of any two numbers of 1h, 1.5h, and 2h; the heating rate of the first step heat treatment can be any value within the numerical range composed of any two numbers of 5℃ / min, 7℃ / min, 9℃ / min, 11℃ / min, 13℃ / min, and 15℃ / min.

[0028] The temperature of the second step heat treatment can be any value within the numerical range formed by any two numbers of 800℃, 850℃, 900℃, 950℃, and 1000℃; the time of the second step heat treatment can be any value within the numerical range formed by any two numbers of 1h, 1.5h, and 2h; the heating rate of the second step heat treatment can be any value within the numerical range formed by any two numbers of 5℃ / min, 7℃ / min, 9℃ / min, 11℃ / min, 13℃ / min, and 15℃ / min.

[0029] The temperature of the third step heat treatment can be any value within the numerical range formed by any two numbers of 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, and 1200°C; the time of the third step heat treatment can be any value within the numerical range formed by any two numbers of 1h, 1.5h, and 2h; the heating rate of the third step heat treatment can be any value within the numerical range formed by any two numbers of 5°C / min, 7°C / min, 9°C / min, and 10°C / min.

[0030] The temperature of the fourth step heat treatment can be any value within the numerical range composed of any two numbers among 1300℃, 1350℃, 1400℃, 1450℃, 1500℃, etc.; the time of the fourth step heat treatment can be any value within the numerical range composed of any two numbers among 50min, 70min, 900min, 110min, 130min, 150min, etc.; the heating rate of the fourth step heat treatment can be any value within the numerical range composed of any two numbers among 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min.

[0031] In some embodiments, preferably, the concentration of the acidic solution is 0.5-1.5 mol / L. There is no special requirement for the type of the acidic solution, such as hydrochloric acid, and the concentration of the acidic solution can be any value within the numerical range consisting of any two numbers of 0.5 mol / L, 1 mol / L, and 1.5 mol / L.

[0032] The present invention has no particular requirement on the type of inert gas, and it may be argon, for example.

[0033] The room temperature of the present invention is 20-25°C.

[0034] In some embodiments, preferably, the gluconate is selected from one or more of zinc gluconate, calcium gluconate, sodium gluconate, ferrous gluconate, and magnesium gluconate. The above raw materials are cheap and easy to obtain, which is conducive to reducing costs.

[0035] In some embodiments, preferably, the preparation method further comprises: performing ultrasonic treatment while performing the soaking, and the soaking time is 0.5-2h. Ultrasonic treatment is used to improve the removal speed and removal efficiency of metal elements during soaking. There is no special requirement for the ultrasonic intensity of the ultrasonic treatment, such as 30W, 40W, etc., and the ultrasonic treatment time can be any value within the numerical range of any two numbers of 0.5h, 1h, 1.5h, and 2h.

[0036] In some embodiments, preferably, the preparation method further comprises: washing the collected material with deionized water to neutrality after the fourth step of heat treatment, and drying to obtain the hard carbon negative electrode material.

[0037] A second aspect of the present invention provides a hard carbon negative electrode material, which is prepared according to the preparation method described in the first aspect of the present invention.

[0038] The third aspect of the present invention provides a negative electrode, which comprises the hard carbon negative electrode material prepared by the preparation method described in the first aspect of the present invention or the hard carbon negative electrode material described in the second aspect of the present invention.

[0039] A fourth aspect of the present invention provides a lithium-ion battery, comprising the negative electrode described in the third aspect of the present invention.

[0040] The present invention introduces a large number of pore structures into the prepared hard carbon negative electrode material through staged carbonization and acid washing, and makes a part of these pore structures form closed-pore structures. The prepared hard carbon negative electrode material shows excellent cycle performance. In the first week of charge and discharge cycle under 0.1C conditions, the charging specific capacity is not less than 320mAh / g. At a 1C rate, the reversible specific capacity of the prepared hard carbon negative electrode material is not less than 250mAh / g after 300 cycles, and the cycle performance is stable, and the cycle coulomb efficiency is not less than 99%, which is close to 100%.

[0041] The present invention will be described in detail below by way of examples. In the following examples and comparative examples, unless otherwise specified, the reagents or instruments used without indicating the manufacturer are conventional products that can be purchased commercially. If no specific conditions are indicated in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed.

[0042] The constant current charge and discharge test of the battery adopts Land CT2001A produced by Wuhan Landian Electronics Co., Ltd.

[0043] Example 1 (1) Weigh 10 g of zinc gluconate and put it into a porcelain boat. Pass argon gas in a tube furnace for 30 minutes. Heat from room temperature to 400°C at a heating rate of 10°C / min under argon flow, keep warm for 1 hour, then continue to heat to 900°C at a heating rate of 10°C / min, keep warm for 1 hour, and naturally cool to room temperature to obtain a precursor.

[0044] (2) The precursor was crushed into powder in a mortar while hot, and then immersed in a 1 M HCl solution, assisted by ultrasonic treatment (ultrasonic intensity 30 W), filtered after 1 hour, and then washed with deionized water until neutral, washed three times with ethanol, and then vacuum dried at 110 ° C for 12 hours to obtain an intermediate.

[0045] (3) The intermediate after drying in step 2 is heated from room temperature to 1100°C at a heating rate of 5°C / min under argon flow, and kept at this temperature for 2 hours, then continued to be heated to 1500°C at a heating rate of 2°C / min, and kept at this temperature for 100 minutes, and then naturally cooled to room temperature.

[0046] (4) The material collected in step 3 was washed three times with deionized water and ethanol, and then dried in vacuum at 80°C for 12 h to obtain a zinc gluconate-derived hard carbon negative electrode material, which was recorded as A1.

[0047] The SEM image of the material obtained in this embodiment is as follows: Figure 1 and 2 As shown in the figure, it can be seen that the hard carbon negative electrode material has an irregular porous structure on the surface, and its SED diagram is as follows Figure 3 As shown, it can be seen that the prepared hard carbon negative electrode material no longer contains zinc element, and mainly contains C and O elements, and the C and O elements are evenly distributed, indicating that the method successfully obtains hard carbon and the sample does not contain other impurities. The ZnO nanoparticles are successfully removed, leaving a large number of pores.

[0048] The first week charge and discharge curve of the hard carbon negative electrode material at a current density of 0.1C (1C=300mAh / g) in the voltage window of 0.01V~1.5V is as follows: Figure 4 As shown, the cycle diagram of 1C current density in the voltage window of 0.01V~1.5V is as follows Figure 5 As shown. Combined Figure 4 and Figure 5It can be seen that the hard carbon negative electrode material prepared in this embodiment exhibits excellent cycle performance. In the first week of charge and discharge cycle under 0.1C conditions, the charging specific capacity is as high as 338.94 mAh / g. At a rate of 1C, the reversible specific capacity of the prepared hard carbon remains at 272.2 mAh / g after 300 cycles, and the cycle performance is stable, and the cycle coulombic efficiency is close to 100%.

[0049] Example 2 (1) Weigh 10 g of magnesium gluconate and put it into a porcelain boat. Pass argon gas in a tube furnace for 30 minutes. Heat from room temperature to 600°C at a heating rate of 5°C / min under argon flow, keep warm for 1.5 hours, then continue to heat to 800°C at a heating rate of 5°C / min, keep warm for 1.5 hours, and naturally cool to room temperature to obtain a precursor.

[0050] (2) The precursor was crushed into powder in a mortar while hot, and then immersed in a 0.5 M HCl solution, assisted by ultrasonic treatment (ultrasonic intensity 30 W), filtered after 2 h, and then washed with deionized water until neutral, washed three times with ethanol, and then vacuum dried at 110 ° C for 12 h to obtain an intermediate.

[0051] (3) The intermediate after drying in step 2 is heated from room temperature to 900°C at a heating rate of 7°C / min under argon flow, and kept at this temperature for 1.5 hours, then continued to be heated to 1300°C at a heating rate of 1°C / min, and kept at this temperature for 150 minutes, and then naturally cooled to room temperature.

[0052] (4) The material collected in step 3 was washed three times with deionized water and ethanol, and then dried in vacuum at 80°C for 12 h to obtain a zinc gluconate-derived hard carbon negative electrode material, which was recorded as A2.

[0053] Example 3 (1) Weigh 10 g of calcium gluconate and put it into a porcelain boat. Pass argon gas in a tube furnace for 30 minutes. Heat from room temperature to 500°C at a heating rate of 15°C / min under argon flow, then keep warm for 2 hours. Then continue to heat to 1000°C at a heating rate of 15°C / min, then keep warm for 2 hours, and naturally cool to room temperature to obtain a precursor.

[0054] (2) The precursor was crushed into powder in a mortar while hot, and then immersed in a 1.5 M HCl solution, assisted by ultrasonic treatment (ultrasonic intensity 30 W), filtered after 0.5 h, and then washed with deionized water until neutral, washed three times with ethanol, and then vacuum dried at 110 ° C for 12 h to obtain an intermediate.

[0055] (3) The intermediate after drying in step 2 is heated from room temperature to 1200°C at a heating rate of 10°C / min under argon flow, and kept at this temperature for 1 hour, then continued to be heated to 1400°C at a heating rate of 5°C / min, and kept at this temperature for 50 minutes, and then naturally cooled to room temperature.

[0056] (4) The material collected in step 3 was washed three times with deionized water and ethanol, and then dried in vacuum at 80°C for 12 h to obtain a zinc gluconate-derived hard carbon negative electrode material, which was recorded as A3.

[0057] Example 4 The process was carried out in the same manner as in Example 1, except that the temperature of the second heat treatment was 600° C. The obtained sample was denoted as A4.

[0058] Example 5 The method of Example 1 was followed, except that the temperature of the second heat treatment was 600° C. and the temperature of the third heat treatment was 700° C. The obtained sample was denoted as A5.

[0059] Example 6 The process was carried out in the same manner as in Example 1, except that the heating rate of the first step of heat treatment was 2°C / min, and the obtained sample was denoted as A6.

[0060] Example 7 The process was carried out in the same manner as in Example 1, except that the heating rate of the first step of heat treatment was 20° C. / min, and the obtained sample was denoted as A7.

[0061] Example 8 The process was carried out in the same manner as in Example 1, except that the heating rate of the second step heat treatment was 2°C / min, and the obtained sample was denoted as A8.

[0062] Example 9 The process was carried out in the same manner as in Example 1, except that the heating rate of the second step heat treatment was 20°C / min, and the obtained sample was denoted as A9.

[0063] Example 10 The process was carried out in the same manner as in Example 1, except that the heating rate of the third step heat treatment was 2°C / min, and the obtained sample was denoted as A10.

[0064] Embodiment 11 The process was carried out in the same manner as in Example 1, except that the heating rate of the third step heat treatment was 15°C / min, and the obtained sample was denoted as A11.

[0065] Example 12 The process was carried out in the same manner as in Example 1, except that the heating rate of the fourth step heat treatment was 8°C / min, and the obtained sample was denoted as A12.

[0066] Embodiment 13 The process was carried out in the same manner as in Example 1, except that the holding time for the first step of heat treatment was 3.5 h, and the obtained sample was denoted as A13.

[0067] Embodiment 14 The process was carried out in the same manner as in Example 1, except that the holding time for the second step of heat treatment was 3.5 h, and the obtained sample was denoted as A14.

[0068] Embodiment 15 The process was carried out in the same manner as in Example 1, except that the holding time for the third step of heat treatment was 3.5 h, and the obtained sample was recorded as A15.

[0069] Example 16 The process was carried out in the same manner as in Example 1, except that the holding time for the fourth step of heat treatment was 20 min, and the obtained sample was denoted as A16.

[0070] Embodiment 17 The process was carried out in the same manner as in Example 1, except that the holding time of the fourth step heat treatment was 200 min, and the obtained sample was recorded as A17.

[0071] Comparative Example 1 The process was carried out in the same manner as in Example 1, except that the temperature of the first heat treatment step was 300° C. The obtained sample was denoted as D1.

[0072] Comparative Example 2 The process was carried out in the same manner as in Example 1, except that the temperature of the first heat treatment step was 700° C. The obtained sample was denoted as D2.

[0073] Comparative Example 3 The process was carried out in the same manner as in Example 1, except that the temperature of the second heat treatment was 400° C. The obtained sample was denoted as D3.

[0074] Comparative Example 4 The process was carried out in the same manner as in Example 1, except that the temperature of the third step heat treatment was 900° C. and the obtained sample was denoted as D4.

[0075] Comparative Example 5 The process was carried out in the same manner as in Example 1, except that the temperature of the fourth step heat treatment was 1200° C. and the obtained sample was denoted as D5.

[0076] Comparative Example 6 The process was carried out in the same manner as in Example 1, except that the temperature of the fourth step heat treatment was 1600°C, and the obtained sample was denoted as D6.

[0077] Comparative Example 7 (1) Weigh 10 g of zinc gluconate and put it into a porcelain boat. Pass argon gas in a tube furnace for 30 minutes. Heat from room temperature to 600°C at a heating rate of 10°C / min under argon flow, then keep warm for 2 hours and naturally cool to room temperature to obtain a precursor.

[0078] (2) The precursor was crushed into powder in a mortar while hot, and then immersed in a 1 M HCl solution, assisted by ultrasonic treatment (ultrasonic intensity 30 W), filtered after 1 h, and then washed with deionized water until neutral, washed three times with ethanol, and then vacuum dried at 110 ° C for 12 h to obtain an intermediate.

[0079] (3) The intermediate obtained after drying in step 2 was heated from room temperature to 1300° C. at a heating rate of 5° C. / min under an argon flow, and kept at this temperature for 3.6 h, and then cooled naturally to room temperature.

[0080] (4) The material collected in step 3 was washed three times with deionized water and ethanol, and then dried in vacuum at 80 °C for 12 h to obtain a zinc gluconate-derived hard carbon negative electrode material, which was recorded as D7.

[0081] The materials obtained in the above Examples 1-17 and Comparative Examples 1-7 were used to assemble and test batteries. The specific operations are as follows: The slurry obtained by mixing the sample materials (Examples 1-17 and Comparative Examples 1-7): Super P: PAA (binder, polyacrylic acid aqueous solution) in a mass ratio of 8:1:1 was coated on a copper foil using a 125 μm scraper to form a pole piece. A metal sodium sheet was used as the counter electrode, and 1M LiPF 6 The diethylene glycol dimethyl ether solution is the electrolyte (wherein the solvent is diethylene glycol dimethyl ether and the solute is LiPF 6 ), assembled into a 2032 button cell in an argon glove box. Then the battery was left to stand for 10 h, tested at 30°C, with a voltage range of 0.01V-1.5V, cycled 5 times at a current density of 0.1C (1C=300mA / g), and then cycled to 300 times at a rate of 1C. The test results are shown in Table 1.

[0082] Table 1 Test results

[0083] It can be seen from the results in Table 1 that the first-cycle coulombic efficiency and charge specific capacity of the hard carbon material prepared by the present invention are significantly improved, and it still has a high reversible specific capacity after 300 cycles at 1C.

[0084] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a hard carbon negative electrode material, characterized in that: After subjecting the gluconate to a first heat treatment in an inert gas atmosphere, the gluconate is then immersed in an acidic solution to remove metal elements to obtain an intermediate, and the intermediate is subjected to a second heat treatment in an inert gas atmosphere to obtain a hard carbon negative electrode material; The first heat treatment process includes: a first heat treatment and a second heat treatment performed sequentially, wherein the temperature of the first heat treatment is 400-600°C, the time is 1-2h, and the temperature of the second heat treatment is higher than the temperature of the first heat treatment; The second heat treatment process includes: a third heat treatment and a fourth heat treatment performed in sequence, wherein the temperature of the third heat treatment is higher than the temperature of the second heat treatment and lower than the temperature of the fourth heat treatment, and the temperature of the fourth heat treatment is 1300-1500°C and the time is 50-150min.

2. The preparation method according to claim 1, wherein The difference between the temperature of the second heat treatment and the temperature of the first heat treatment is not less than 200°C; and / or, the difference between the temperature of the third step heat treatment and the temperature of the second step heat treatment is not less than 100° C.; And / or, the difference between the temperature of the fourth step heat treatment and the temperature of the third step heat treatment is not less than 100°C.

3. The preparation method according to claim 1 or 2, wherein The second step of heating is performed at a temperature of 800-1000°C for 1-2 hours; And / or, the temperature of the third step heat treatment is 900-1200° C. and the time is 1-2 hours.

4. The preparation method according to any one of claims 1 to 3, wherein The heating rate of the first step heat treatment is 5-15°C / min; And / or, the heating rate of the fourth step heat treatment is 1-5°C / min.

5. The preparation method according to any one of claims 1 to 4, wherein: The heating rate of the second heat treatment is 5-15°C / min; And / or, the heating rate of the third step heat treatment is 5-10°C / min.

6. The preparation method according to any one of claims 1 to 5, wherein: The concentration of the acidic solution is 0.5-1.5 mol / L; And / or, the gluconate is selected from one or more of zinc gluconate, calcium gluconate, sodium gluconate, ferrous gluconate, and magnesium gluconate.

7. The preparation method according to any one of claims 1 to 6, wherein: The preparation method further comprises: performing ultrasonic treatment while performing the soaking, wherein the soaking time is 0.5-2h; And / or, the preparation method further comprises: washing the collected material with deionized water to neutrality after the fourth step of heat treatment, and drying to obtain the hard carbon negative electrode material.

8. A hard carbon negative electrode material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.

9. A negative electrode, characterized in that It comprises the hard carbon negative electrode material prepared by the preparation method described in any one of claims 1 to 7 or the hard carbon negative electrode material described in claim 8.

10. A lithium ion battery, characterized in that: Comprising the negative electrode as claimed in claim 9.

Citation Information

Patent Citations

  • Preparation method of self-supporting nitrogen-doped hard carbon negative electrode material

    CN110048107A

  • Nitrogen-doped porous hard carbon material based on rosin as well as preparation method and application of nitrogen-doped porous hard carbon material

    CN116239100A

  • Hard carbon material, preparation method and application thereof, and secondary battery

    CN116534838A